A Māori love story: Community-led disaster management in response to the Ōtautahi (Christchurch) earthquakes as a framework for action. (December 2015) - Kenney, Christine M.; Phibbs, Suzanne
Abstract: Within the disaster response and research sectors, there is increasing recognition of the value of community-led initiatives that facilitate emergency management, risk reduction and community resilience. In contrast, the value of cultural approaches to disaster management and recovery is rarely acknowledged. The Māori disaster management response to the Christchurch earthquakes and subsequent urban recovery process constitutes an exemplar of best practice. During the emergency management phase, Māori risk management initiatives were collaborative, effective and shaped by kaupapa (cultural values), specifically the value, 'aroha nui ki te tangata' (extend love to all people). In this article, the potential value of Māori kaupapa-based technologies for shaping contextually relevant disaster management and risk reduction strategies is considered. The discussion draws from research findings arising from two projects conducted by the Joint Centre of Disaster Research in partnership with Te Rūnanga o Ngāi Tahu (resident Māori tribe) that address Māori disaster–related concerns, including factors that facilitate community recovery. An overview of the Māori emergency response, including perceived hindrances, is provided as background. Drawing upon frameworks provided within Actor-Network Theory cultural technologies that facilitate community well-being and recovery are identified and the ways in which technologies were operationalised within the emergency context, outlined. With reference to the Hyogo Framework for Action the applicability of integrating Māori technologies into national civil defence emergency management policies is also discussed and recommendations are proposed for adapting and implementing these technologies as a component of integrated disaster risk reduction at the local, national and international levels.